Familial steroid‐resistant nephrotic syndromes: recent advances - Fuchshuber, Arno; Mehls, Otto (Nephrology, dialysis, transplantation, 2000)
Nephrotic syndrome (NS) usually occurs as a sporadic disease, but familial cases have frequently been reported. The first observation in six families with 13 af
Gesehen am 12.01.2021